Aesthetic experiences and flourishing in science: A four-country study - Jacobi, Christopher J.; Varga, Peter J.; Vaidyanathan, Brandon (Frontiers in Psychology, 2022)
In response to the mental health crisis in science, and amid concerns about the detrimental effects of the COVID-19 pandemic on scientists, this study seeks to identify the role of a heretofore under-researched factor for flourishing and eudaimonia: aesthetic experiences in scientific work. The main research question that this study addresses is: To what extent is the frequency of encountering aesthetics in terms of beauty, awe, and wonder in scientific work associated with greater well-being among scientists? Based on a large-scale (N = 3,061) and representative international survey of scientists (biologists and physicists) in four countries (India, Italy, the United Kingdom, the United States), this study employs sets of nested regressions to model the associations of aesthetic experiences with flourishing while controlling for demographic factors and negative workplace and life circumstances such as burnout, job/publication pressure, mistreatment, COVID-19 impacts, other stressful life events, serious psychological distress, and chronic health conditions. The results show that the frequency of aesthetic experiences in scientific work in the disciplines of biology and physics has a very large and statistically significant association with flourishing and eudaimonia that remains robust even when controlling for demographic and negative workplace and life circumstances, including COVID-19 impacts. Aesthetic experiences in scientific work are even as strongly associated with flourishing as the presence of serious psychological distress and are most strongly associated with the flourishing domain of meaning in life, thus pointing to a link with eudaimonic well-being. In line with neurophysiological evidence and positive psychological models of flow, self-transcendence, and intrinsic motivation, aesthetics are a key source of flourishing for scientists in the disciplines of biology and physics. While future research needs to test the causal mechanism, the strength of the findings could encourage leaders of scientific labs and research organizations generally to remove obstacles to experiencing the aesthetic dimensions of science. Fostering cultures in which the aesthetic experiences that are intrinsic to scientific practice are fully appreciated might potentially protect or boost flourishing by reducing the impacts of burnout, job/publication pressure, and mistreatment-related experiences in science.